Bench press exercise performed as conditioning activity improves shot put performance in untrained subjects - Diego de Alcantara Borba; João Batista Ferreira-Júnior; Marcos Vinicius Dias Ramos; Rafael de Leon Dumont Gomes; Juliana Bonhen Guimarães; João Roberto Ventura de Oliveira (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: The aim of the present study was to evaluate the effect of bench press exercise performed as conditioning activity on the shot put performance in untrained subjects. Methods: Twelve healthy men (26 ± 6 years; 1.8 ± 0.1 m; 73.5 ± 10.4 kg; 13.2 ± 5.2% body fat), with no experience in shot put, were randomly assigned into two conditions: 1) Control: subjects performed six shot put attempts, and 2) Bench press exercise: subjects performed six shot put attempts 7 min post 2 sets of 5 repetitions maximum (RM) of bench press exercise. A metal ball of 4 kg was used for shot put attempts, and subjects were instructed to perform each shot put according to the static shot put technique. Results: Shot put performance was greater after bench press condition when compared with control condition (8.2 ± 1.2 m vs. 7.8 ± 0.8 m, respectively, p < 0.05). In addition, eight out of 12 volunteers positively responded to the conditioning activity. Conclusion: The results suggest that bench press exercise performed as a conditioning activity improves shot put performance in untrained subjects. Moreover, the conditioning activity should be individually set.